A psychotherapeutically oriented approach to vibroacoustic therapy : therapy process with a client diagnosed with functional neurological disorder experiencing dissociative symptoms - Leandertz, Mikaela (2018)
Functional Neurological Disorder (FND) is a somatic symptom disorder that affects a significant number of people worldwide with a large variety of experienced symptoms and comorbid disorders. FND is diagnosed in patients who present physiological symptoms without a neurological or medical condition. This master’s thesis describes the therapy process of a patient diagnosed with FND, utilizing a psychotherapeutically-oriented approach to vibroacoustic therapy as the primary clinical protocol. The client in this case was diagnosed with FND by a neurologist and referred to the music therapist. In addition to the experience of occasional paralysis attacks, the client experienced regular dissociative symptoms. The client’s experience of depersonalization also contributed to her experience of functional weakness; a weakness down one side of the body. Though the client experienced sensations of both depersonalization and derealization on a regular basis throughout the therapeutic process during the vibroacoustic treatment, the safety and security existant within the therapeutic environment enabled the client to experience and explore these symptoms without the usual accompanying anxiety and panic. The therapeutic protocol outlined in this paper is interdisciplinary and diverse. It includes an interdisciplinary referral process, as well as the utilization of therapeutic approaches from music therapy, vibroacoustic therapy, psychotherapy, and trauma theory. During the therapeutic process, the client was able to address and further explore her FND symptoms in multiple mediums. The patient showed great improvement in integration of the different parts of her Self, confidence, and emotional expression, and has been able to implement strategies developed in her sessions to everyday situations outside of therapy. These tools have allowed the patient to identify emotions and/or triggers, reduce feelings of anxiety and panic initiated by her dissociative symptoms, and thus reduce the risk for further paralysis attacks.